Globalization and Market Development in Crisis - Maśloch, Piotr (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
Admiration for globalization. Globalization as a method of solving all social problems. Victory of the global market economy and self-control of the global economy. These such serious problems concerning the correlation between modern globalization and an economy in crisis are leading contents of this article. It shows the nature of modern globalization with a detailed analysis, which presents in what way these phenomena influence changes in the global economy and global crisis.